Normal Island: COVID-19, Border Control, and Viral Nationalism in UK Public Health Discourse. (June 2023) - Fitzgerald, Des
In this contribution, I present emergent analysis of a preoccupation with managing COVID-19 through border control, among non-Governmental public health actors and commentators. Through a reading of statements, tweets, and interviews from the 'Independent Sage' group – individually and collectively – I show how the language of border control, and of maintaining immunity within the national boundaries of the UK, has been a notable theme in the group's analysis. To theorize this emphasis, I draw comparison with the phenomenon of 'green nationalism', in which the urgency of climate action has been turned to overtly nationalistic ends; I sketch the outlines of what I call 'viral nationalism, ' a political ecology that understands the pandemic as an event occurring differentially between nation states, and thus sees pandemic management as, inter alia, a work of involuntary detention at securitized borders. I conclude with some general remarks on the relationship between public health, immunity, and national feeling in the UK.